Sustaining continuous professional development for quality teaching and learning in higher education: The role of policy and policy implementers - Annyza Tumar, *; Asimiran, Soaib; Pihie, Zaidatol Akmaliah Lope; Ismi Arif, Ismail (Turkish Online Journal of Educational Technology, Turkey, 2015)
Continuous professional development (CPD) is important for academics to improve the quality of their teaching and their students’ learning. This paper reports the findings of a qualitative case study on CPD support at a Malaysian private university. It reports the perceptions of institutional leaders and academics on existing CPD support and how such support can be increased. Data was derived from interviews and teaching observations while factual verification was obtained through document analysis. Findings indicated the institution was supportive of its academics’ CPD needs through top-down measures including policies and guidelines, and provision of different on-site CPD models. However, there were some gaps between areas of CPD needs and areas supported. One implication was that existing policy gap could be reduced through policy review and revision. Another implication was a need for academic heads to go beyond their role as policy implementers by identifying, initiating and supporting specific CPD needs at the departmental level.